Perancangan Antena 4G Untuk Mobile Handset Pada Frekuensi 2.3 GHz - Rahmat Deni; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Microstrip antenna as a communication device has small dimension with good receiving signal ability, this microstrip antenna is a technology that can be used on a wireless network application with high rate data speed. Microstrip antenna is very suitable for long term evolution applications. This microstrip antennas are small, designed in such a way that can be used daily without causing bad image effects for user appereance. The antenna is designed by using CST STUDIO SUITE software, the designed result are : frequ…ency 2.3 GHz with return loss ≤ -10 dB, and VSWR ≤ 2.Keyword : microstrip antenna, long term evolution for handset, return loss and VSWR.